Spectrophotometric Evaluation of Natural Tooth Color Distribution Across Three Dental Shade Guide Systems: A Cross-Sectional Study - Zarkova Atanasova, Julija; Zlatanovska, Katerina; Proseva Pelivanova, Ljubica; Atanasova, Sandra; Nikolovski, Bruno; Longurova, Natasha; Apostoloski, Pavle (European Scientific Journal, ESJ, 2026)
Accurate determination of tooth color is essential for achieving optimal esthetic outcomes in restorative dentistry. Spectrophotometry has emerged as a reliable method for objective color assessment, overcoming the limitations of visual shade selection. This study aimed to evaluate the distribution of natural tooth color using spectrophotometric measurements, to compare its representation across three dental shade guide systems, and to assess its variation according to gender and age. A total of 235 participants aged 18–69 years were included in this cross-sectional study. Tooth color of maxillary central incisors was measured using a non-contact spectrophotometer (ShadePilot). The obtained values were matched to VITA Classical, Ivoclar Chromascop, and VITA 3D-Master shade guides. Statistical analysis was performed using the Pearson Chi-square test (p < 0.05). Shades from Group A (VITA Classical), Group 100 (Chromascop), and Group 2 (VITA 3D-Master) were the most prevalent. Significant differences in shade distribution were observed across all three systems. Both gender and age showed statistically significant influence on tooth color (p < 0.05), with a clear trend toward darker shades in older age groups. Natural tooth color distribution varies depending on the shade guide system used and is significantly influenced by demographic factors. Spectrophotometric analysis provides a reliable approach for improving shade selection and enhancing esthetic outcomes in clinical practice.